1999
DOI: 10.1590/s0037-86821999000400009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de parasitismo intestinal nas aldeias indígenas da tribo Tembé, Amazônia Oriental Brasileira

Abstract: To determine the prevalence of intestinal parasitism in the Tembé settlements, parasitological examination was performed in December 1996 in the entire population (93 Indians). Hookworms were found in 29.0%, A. lumbricoides in 34.4%, E. histolytica in 12.9%, and G. lamblia in 4.3% of the individuals. The Turé-Mariquita settlement had the highest prevalence of hookworms and A. lumbricoides, while Acará-Mirim had the highest prevalence of E. histolytica and G. lamblia. No differences in mean age were found betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
0
2
1
7
Order By: Relevance
“…The medicines used in the villages, including, in particular, the products used against intestinal parasites, were exclusively those prescribed and distributed free of charge by the nurse and the health care agents of the clinic at Zidock. Three recent studies on the Indians of Brazilian Amazonia (Ferrari et al, 1992;Miranda et al, 1999) and central Brazil (Santos et al, 1995) reported frequencies of parasitism lower than those reported here, except for…”
Section: The Prevalences Of Infection With Strongyloides Andcontrasting
confidence: 73%
“…The medicines used in the villages, including, in particular, the products used against intestinal parasites, were exclusively those prescribed and distributed free of charge by the nurse and the health care agents of the clinic at Zidock. Three recent studies on the Indians of Brazilian Amazonia (Ferrari et al, 1992;Miranda et al, 1999) and central Brazil (Santos et al, 1995) reported frequencies of parasitism lower than those reported here, except for…”
Section: The Prevalences Of Infection With Strongyloides Andcontrasting
confidence: 73%
“…A prevalência de enteroparasitoses também está associada à contaminação das fontes de água em virtude deste destino 13 inadequado de dejetos e o consumo de água sem tratamento favorece a transmissão de enteroparasitoses 13,14,15 entre os indígenas . Adicionalmente, o clima úmido e solo arenoso de algumas áreas da Região Amazônica também favorecem a manutenção de estágios infectantes 9,14 de parasitas em determinados ambientes .…”
Section: Discussionunclassified
“…Nesta pesquisa, observou-se que a população idosa apresentou uma maior percentagem de monoparasitismo (43,2%), enquanto que estudos em crianças e jovens mostraram predominância de poliparasitismo (Araujo & Correia, 1997;Coura et al, 1993), provalvemente devido a que essas faixas etárias apresentam maior exposição a solos contaminados, especialmente na ausência de calçados (Miranda et al, 1999).…”
Section: Ocorrência De Enteroparasitas Na População Geronte De Nova Ounclassified